All optical XOR logic gates technologies and experiment demonstrations. - Min Zhang; Ling Wang.; Peida Ye.
This article reviews the current status and technologies of all-optical XOR gates. Various schemes with semiconductor optical amplifiers, particularly those associated with interferometric structures, are discussed and compared. Finally, the applications of all-optical XOR gates to emerging networks are explored, and the future direction is outlined.
Keywords: all optical XOR logic gate; interferometric structure; semiconductor optical amplifier